Implications of Behavioral Science for Managerial Accounting. - Birnberg, Jacob G.; Nath, Raghu (The Accounting Review, 1967)
Abstract This article focuses on a study which investigated the implications of behavioral science for managerial accounting. Accountants have been involved with the behavioral dimension of accounting problems for quite some time. The management information system of any firm is not solely a technical communication system, one designed only to permit data to flow from one point in the system (i.e., the firm) to another. Very little research has been done on the form of the relationships between the organization and the individual and its implication for accounting data. A more decentralized form of organization would, he conjectured, ease many of the accounting problems by refocusing the attention of supervisors to other, less arbitrary sets of data. The study of management control systems has progressed in three areas: the problems in standard setting, the impact of the audit function, and the reporting of relevant data.